Kant’s Anniversary in Light of Recent publications in “Sententiae” (2020–2024) - Ivan Ivashchenko (Kyiv-Mohyla Humanities Journal)
Kant’s Аnniversary in Light of Recent Publications in Sententiae (2020–2024)